An evaluation of economic viability of small scale slaughterhouses in Vietnam: Implication for pig value chain development - Nguyen Thi Duong Nga; Lapar, Ma. Lucila; Pham Van Hung; Tran Van Long; Pham Kieu My; Pham Thi Toan; Unger, Fred (Kasetsart University, 2017)
Slaughterhouse plays important role in pig value chain in Vietnam, not only for the functions it plays and economic added value it generates, but also for product quality relates to food safety standards that is much affected under slaughtering activity. The study is aimed to get a better understanding of structure, conduct, performance and economic viability of small scale slaughter houses in the pig value chain, and draw key implications for pig value chain development in Vietnam. Nghe An and Hung Yen are selected as study site. Data is collected from 51 small scale slaughterhouses in 18 communes. Descriptive and comparative statistics are employed with t-test for mean comparison. Results show that slaughterhouse plays multiple functions in the pig value chain, generate permanent jobs for at least 2 family labors, and provides an income of about 18 USD/working day for family labor, contributing about threefourths of total family income. Slaughtering activity generates an added value of 165 USD/one ton of live pig, accounting from 24%-44% total value added in the pig value chain. Upstream and downstream linkages of slaughterhouses in the chain are quite loose with no formal contract. The majority of small scale slaughterhouses do not meet the standards for pig slaughterhouse as required by the Ministry of Agriculture and Rural Development. The setting up as well as slaughtering practices are perceived to contribute to exposure of meat to contamination that could lead to higher incidence of salmonella in pork, a common cause of foodborne illness for consumers. Rising concerns of consumers about food safety as well as increasing level of economic integration of Vietnam are factors potentially having great impacts on economic viability of small scale slaughterhouse in Vietnam. Several recommendations for upgrading slaughterhouse are proposed accordingly.